Impaired prothrombinase activity of factor X Gly381Asp results in severe familial CRM+ FX deficiency - Pinotti, Mirko; Camire, Rodney M.; Baroni, Marcello; Rajab, Anna; Marchetti, Giovanna; Bernardi, Francesco (Thrombosis and Haemostasis, 2003)
We investigated three members of a large Omani family affected by severe factor X (FX) deficiency (coagulant activity <1%) and showing marked differences in the onset of severe hemorrhagic symptoms. All patients were homozygous for a novel FX mutation (Gly381Asp) in the structurally conserved region of the serine protease active site. Expression levels of recombinant 381D-FX were similar to those of wt-FX, indicating the presence of a severe CRM+ FX deficiency, a poorly investigated condition. The 381D-FX was normally activated and did not show a detectable amidolytic activity. Instead, we observed a residual activity in a prothrombin-time based assay (1%) and in prothrombinase assays both in plasma (1%) and in purified systems (3%). Comparison with FX variants characterized by reduced activation suggests that mutations affecting FX activity might result in a more pronounced impairment of coagulation and thus in severe hemorrhagic phenotype. In addition, this study indicates that the hemorrhagic heterogeneity observed in FX deficiencies is only partially explained by molecular analysis of FX gene.
Keywords: CRM+ FX deficiency; hemorrhagic phenotype; recombinant FX; FX activity